A preliminary investigation into the use of acid-treated Salmonella minnesota R595 bacteria as immune carriers for oral vaccines - Bishop, Bernard Deon (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 1991.